2012
DOI: 10.1111/j.1582-4934.2011.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin regulation of cytoskeleton organization: a new paradigm to analyse the effects of calcineurin inhibitors on the kidney

Abstract: Calcineurin is a serine/threonine phosphatase originally involved in the immune response but is also known for its role as a central mediator in various non-immunological intracellular signals. The nuclear factor of activated T cell (NFAT) proteins are the most widely described substrates of calcineurin, but ongoing work has uncovered other substrates among which are the cytoskeleton organizing proteins (i.e. cofilin, synaptopodin, WAVE-1). Control over cytoskeletal proteins is of outmost interest because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 95 publications
2
23
0
Order By: Relevance
“…2B), consistent with the known roles of CN to dephosphorylate transcription factors and DNA binding proteins that are critical for the G1-S transition of the cell cycle2122. The large distribution of πɸLxVP-proteins in the membrane (18%) and intracellular transport (13%) is also consistent with the prominent roles of CN in ion transport and vesicle trafficking, respectively2324.…”
Section: Resultssupporting
confidence: 75%
“…2B), consistent with the known roles of CN to dephosphorylate transcription factors and DNA binding proteins that are critical for the G1-S transition of the cell cycle2122. The large distribution of πɸLxVP-proteins in the membrane (18%) and intracellular transport (13%) is also consistent with the prominent roles of CN in ion transport and vesicle trafficking, respectively2324.…”
Section: Resultssupporting
confidence: 75%
“…CNIs have also been suggested to be cytoprotective in podocytes through the inhibition of synaptopodin degradation and stabilization of the podocyte actin cytoskeleton [28]. Cyclosporine has also been shown to induce stiffening of the actin network in tubular structure, which may alter the response of proximal cells to modifications of tubular flow, potentially exerting a detrimental effect on tubular structure [29]. The physiologic role of calcineurin in kidney cells had largely remained unknown until the exhibition of abnormal kidney development in mice with knockouts for the calcineurin Aα subunit [30].…”
Section: Discussionmentioning
confidence: 99%
“…In PTC, we demonstrated that the actin cytoskeleton could be modified by CsA. 42 Indeed, independently from the inhibition of NFAT, CsA triggered a reversible disorganization of actin scaffolding at the periphery of the cell. Whether a mechanism involving the CsA-related regulation of CFL was responsible for the effects of CsA on PTC remained to be addressed.…”
Section: Discussionmentioning
confidence: 87%
“…In the light of early observations of CsA effects on the actin cytoskeleton of podocytes, the study of the actin dynamic in PTC appeared of utmost interest in the elucidation of pathophysiological mechanisms of TA upon CNI exposure. In PTC, we demonstrated that the actin cytoskeleton could be modified by CsA . Indeed, independently from the inhibition of NFAT, CsA triggered a reversible disorganization of actin scaffolding at the periphery of the cell.…”
Section: Discussionmentioning
confidence: 89%